User-fee-funded stormwater programs (Water Environment Federation, 2013)
A must-read for agencies and public works departments interested in developing charge systems for stormwater programs based on fee structures. This book will specify the drivers for stormwater user-fee formation and explore the responsibilities, costs, and entire implementation process.
Previous edition titled, "User-fee-funded stormwater utilities."
Keywords: Storm sewers -- United States -- Finance.; Sewage disposal -- Rates -- United States.; Storm sewers -- United States -- Finance -- Case studies.; Sewage disposal -- Rates -- United States -- Case studies.; elektronické knihy; electronic books